COMPOSITION SPECIES AND PERCENTAGE OF MACROALGAE COVERAGE IN CORAL REEF ECOSYSTEMS ITS RELATION TO OCEANOGRAPHIC CONDITIONS OF THE WATERS AROUND LAE-LAE AND BARRANGLOMPO ISLANDS - Rhojim Wahyudi; Inayah Yasir; M. Farid Samawi (Universitas Mataram, 2024)
This study aimed to determine the differences in types and percentage coverage of macroalgae and analyze the correlation between the percentage coverage of macroalgal types and oceanographic conditions in the coral reef ecosystem of Lae-lae Island and Barranglompo Island. The study was conducted on November 20, 2011. The sampling technique followed a 50-meter long transect line perpendicular to the coastline. The estimation of macroalgal coverage used the method developed by English (1994), using a 1 x 1 meter plot and a 25 x 25 cm grid, with categories for each grid using a ¼, ½, ¾, and 1 unit scale. Two-Way ANOVA was performed to determine differences in macroalgal coverage, and Canonical Correspondence Analysis (CCA) was used to investigate the relationship between macroalgal coverage and oceanographic conditions. Thirteen species of macroalgae were found on Lae-lae Island, consisting of 8 orders, 9 families, 10 genera, and 13 species, with coverage ranging from 18.58%-53.44%. The two-way ANOVA showed no significant difference in macroalgal coverage between the flat, crest, and slope zones at both stations on Lae-lae Island (P > 0.05). On Barranglompo Island, 7 species were found with a relatively similar composition from 4 orders, 4 families, and 4 genera. The macroalgal coverage on Barranglompo Island ranged from 0%-26.77%. The two-way ANOVA showed that the percentage of macroalgal coverage in the flat, crest, and slope zones for both stations was significantly different (P < 0.05). The oceanographic conditions affecting the high percentage of macroalgal coverage on Lae-lae Island were current speed, temperature, TSS, nitrate (NO3), and on Barranglompo Island were salinity and phosphate (PO4).